(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe road traffic safety (RTS) practices among first-year medical students at Hanoi Medical University and examine selected associated factors. Methods: A cross-sectional, descriptive-analytical study was conducted at the main campus in Hanoi and the Thanh Hoa campus. First-year medical students were selected using stratified random sampling. Data were collected using a self-administered questionnaire, and practice scores were assessed on a five-point Likert scale. Results: Overall RTS practice scores were high, particularly for helmet use, speed compliance, and yielding to pedestrians. Checking vehicle conditions before travel had lower scores compared with other behaviors. No statistically significant differences in practice were found across demographic characteristics (p > 0.05). Conclusions: First-year medical students showed good compliance with road traffic safety practices; however, technical vehicle safety skills should be strengthened through early university-based education programs.